Determination of Nutrients for Potato - T. Aus - T. Aman Rice Cropping Pattern Under Surma Kushiara Flood Plain in AFZ-20 (Bangladesh Agronomy Journal, 2018)
The experiment was carried out in the Surma Kushiyara Floodplain soil at the farmer’s field of Farming System Research and Development (FSRD) site, Jalalpur, under South Surma Upazilla of Sylhet district in the medium high land under agro-ecological zone (AEZ)-20 for the three consecutive years 2013-2016 to determine economic dose of organic and inorganic fertilizers for Potato-T. aus -T. aman rice cropping pattern. The experiment was composed of four treatments viz. T1: Soil test based (STB) fertilizer dose for high yield goal (HYG), T2: T1+ CD 5 t ha-1, T3: T1 along with CD 5 t ha-1 in IPNS approach and T4: Farmers practices for potato-T. aus -T. aman rice cropping pattern maintained in a randomized complete block design with six dispersed replications. The varieties for potato, T. aus and T. aman rice were Diamont, BRRI dhan48 and Binadhan-7, respectively. The results showed that the tuber yield of potato, grain yields of T.aus and of T. aman rice were significantly influenced by the different treatments. The increase yield of tuber 6.11t ha-1 (33.30 %), grain of T. aus 0.42 (10.24%) and T. aman 0.54 (15.52%) rice was obtained from T2 over control (T4) and also higher compared to other treatments. The treatment STB fertilizer for HYG + 5 t ha-1 of CD also showed 25.03% higher T. aman rice equivalent yield (22.53 t ha-1) compared to farmers practice (T4) treatment. The monetary values for the whole cropping pattern showed that the highest benefit cost ratio (2.03), gross return (Tk. 4,61,865 ha-1) and gross margin (Tk.2,33,735 ha-1) were obtained from STB fertilizer for HYG + 5 t ha-1 of CD. The treatment IPNS based on fertilizer management with cowdung for HYG had no significant effect on the yield of first and succeeding crops. So, considering crop productivity and economic return, soil test based fertilizer for high yield goal with 5 t ha-1 cowdung could be recommended for the Potato - T. aus - T. aman rice cropping pattern for AEZ-20 of Sylhet region.Bangladesh Agron. J. 2017, 20(2): 107-113